2014
DOI: 10.1186/1471-2377-14-140
|View full text |Cite
|
Sign up to set email alerts
|

Non-aneurysmal non-traumatic subarachnoid hemorrhage: patient characteristics, clinical outcome and prognostic factors based on a single-center experience in 125 patients

Abstract: BackgroundSubarachnoid hemorrhage (SAH) is mainly caused by ruptured cerebral aneurysms but in up to 15% of patients with SAH no bleeding source could be identified. Our objective was to analyze patient characteristics, clinical outcome and prognostic factors in patients suffering from non-aneurysmal SAH.MethodsFrom 1999 to 2009, data of 125 patients with non-aneurysmal SAH were prospectively entered into a database. All patients underwent repetitive cerebral angiography. Outcome was assessed according to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
62
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 37 publications
14
62
1
3
Order By: Relevance
“…However, in the literature there are conflicting data about gender distribution. Although non aneurysmal SAH was found to be more common in males (5,11), there are also studies suggesting higher prevalence in females (12,13). Nevertheless gender do not influence the disease severity, similar with our findings.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, in the literature there are conflicting data about gender distribution. Although non aneurysmal SAH was found to be more common in males (5,11), there are also studies suggesting higher prevalence in females (12,13). Nevertheless gender do not influence the disease severity, similar with our findings.…”
Section: Discussionsupporting
confidence: 82%
“…The mean age of our patients (58.38±10.91) was similar to that in the current literature (5,9). No significant difference of gender was found between aneurysmal and nonaneurysmal SAHs in our study (10).…”
Section: Discussionsupporting
confidence: 73%
“…2,7,11 More recent data show an increasing number of cases of spontaneous SAH 18,24 as well as nonaneurysmal SAH (NASAH). 15,16 Long-term dipyridamole and warfarin use were associated with an increased risk for aneurysmal SAH (aSAH), whereas the data for low-dose acetylsalicylic acid (LDA) were inconsistent. 10,14,21 Therefore, we analyzed our institutional database for patients suffering from angiography-negative SAH.…”
mentioning
confidence: 99%
“…It has been previously shown that aneurysmal SAH patients had higher mortality rates and Fisher scores suggesting more severe SAH when compared with nonaneurysmal SAH (24,25). Cerebral aneurysm which is associated with vascular or other factors may worsen the amount of bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Turkish Journal of Cerebrovascular Diseases 2018; 24 (1): [19][20][21][22][23][24][25] Comparison of the NLR, PLR and other blood cound parameters of SAH patients with and without cerebral aneurysm has not been studied previously. Therefore, the first aim of this study was to compare these parameters in SAH patients.…”
Section: Introductionmentioning
confidence: 99%